2024
DOI: 10.1007/s13225-023-00529-0
|View full text |Cite
|
Sign up to set email alerts
|

Fungal diversity notes 1717–1817: taxonomic and phylogenetic contributions on genera and species of fungal taxa

Shi-Liang Liu,
Xue-Wei Wang,
Guo-Jie Li
et al.

Abstract: This article is the tenth series of the Fungal Diversity Notes, where 114 taxa distributed in three phyla, ten classes, 30 orders and 53 families are described and illustrated. Taxa described in the present study include one new family (viz. Pseudoberkleasmiaceae in Dothideomycetes), five new genera (Caatingomyces, Cryptoschizotrema, Neoacladium, Paramassaria and Trochilispora) and 71 new species, (viz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 599 publications
(426 reference statements)
0
0
0
Order By: Relevance
“…Currently, MycoBank and Index Fungorum have registered 163 recorded and 156 recorded intraspecific names in Trechispora , respectively. About 100 species are currently accepted in Trechispora worldwide ( Karsten 1890 ; Bondartsev and Singer 1941 ; Rogers and Jackson 1943 ; Rogers 1944 ; Bondartsev 1953 ; Liberta 1966 , 1973 ; Parmasto 1968 ; Burdsall and Gilbertson 1982 ; Gilbertson and Budington 1970 ; Jülich 1975 , 1976 ; Ryvarden 1975 ; Ryvarden and Liberta 1978 ; Hallenberg 1978 , 1980 ; Jülich and Stalpers 1980 ; Rauschert 1987 ; Vries 1987 ; Larsson 1992 , 1994 , 1995 , 1996 ; Hjortstam and Larsson 1995 ; Ryvarden 2002 ; Trichies and Schultheis 2002 ; Ryvarden et al 2003 ; Miettinen and Larsson 2006 ; Dai 2011 ; Yuan and Dai 2012 ; Ordynets et al 2015 ; Phookamsak et al 2019 ; Xu et al 2019 ; Chikowski et al 2020 ; Haelewaters et al 2020 ; Crous et al 2021 ; de Meiras-Ottoni et al 2021 ; Zhao and Zhao 2021 ; Liu et al 2022a , b ; Luo and Zhao 2022 ; Sommai et al 2023 ), of which 38 species of the genus have been found in China ( Dai 2011 ; Yuan and Dai 2012 ; Xu et al 2019 ; Dai et al 2021 ; Zhao and Zhao 2021 ; He et al 2022 ; Liu et al 2022a , b ; Luo and Zhao 2022 ; Deng et al 2023 ; Liu et al 2024a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, MycoBank and Index Fungorum have registered 163 recorded and 156 recorded intraspecific names in Trechispora , respectively. About 100 species are currently accepted in Trechispora worldwide ( Karsten 1890 ; Bondartsev and Singer 1941 ; Rogers and Jackson 1943 ; Rogers 1944 ; Bondartsev 1953 ; Liberta 1966 , 1973 ; Parmasto 1968 ; Burdsall and Gilbertson 1982 ; Gilbertson and Budington 1970 ; Jülich 1975 , 1976 ; Ryvarden 1975 ; Ryvarden and Liberta 1978 ; Hallenberg 1978 , 1980 ; Jülich and Stalpers 1980 ; Rauschert 1987 ; Vries 1987 ; Larsson 1992 , 1994 , 1995 , 1996 ; Hjortstam and Larsson 1995 ; Ryvarden 2002 ; Trichies and Schultheis 2002 ; Ryvarden et al 2003 ; Miettinen and Larsson 2006 ; Dai 2011 ; Yuan and Dai 2012 ; Ordynets et al 2015 ; Phookamsak et al 2019 ; Xu et al 2019 ; Chikowski et al 2020 ; Haelewaters et al 2020 ; Crous et al 2021 ; de Meiras-Ottoni et al 2021 ; Zhao and Zhao 2021 ; Liu et al 2022a , b ; Luo and Zhao 2022 ; Sommai et al 2023 ), of which 38 species of the genus have been found in China ( Dai 2011 ; Yuan and Dai 2012 ; Xu et al 2019 ; Dai et al 2021 ; Zhao and Zhao 2021 ; He et al 2022 ; Liu et al 2022a , b ; Luo and Zhao 2022 ; Deng et al 2023 ; Liu et al 2024a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Most species of the genus grow on angiosperm wood and cause a white rot ( Zhou et al 2016 ). As of early 2024, 49 species are accepted in the genus, 40 species exist in tropical region, and 25 species occur in tropical Asia and Australia ( Tian et al 2013 ; Xavier de Lima et al 2022 ; Wu et al 2022a , b ; Gunaseelan et al 2024 ; Liu et al 2024 ). Tropicoporus excentrodendri L.W.…”
Section: Introductionmentioning
confidence: 99%